Liberalization policy: An empirical analysis of economic and social interventions in Western democracies - Martin Höpner; Alexander Petring; Daniel Seikel; Benjamin Werner (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2014)
Political-economic classics of different schools agreed that capitalism inherently and inevitably leads to a decline of market principles. Analyzing indicators of liberalization policies for 21 OECD-countries in five economic and social policy fields, we demonstrate that Western industrialized countries are subject to a convergent trend towards market-creating policies. This stands in stark contrast to the theoretical expectations of classical works in the field of political economy. Since the first half of the 1980s at the latest, Western democracies have entered a new phase of economic liberalization. From a methodological perspective, our findings suggest that the methods for the causal analysis of convergent liberalization policies cannot be identical with the methods that have been used for analyzing the development and consolidation of the varieties of capitalism in the postwar era.
Keywords: 330